Inside the Next Black Box: Examining Students’ Responses to Teacher Feedback in a Formative Assessment Context - Lui, Angela M.; Andrade, Heidi L. (Frontiers in Education, 2022)
Attempts to explain inconsistencies in findings on the effects of formative assessment and feedback have led us to study the next black box: how students interpret and subsequently use formative feedback from an external source. In this empirical study, we explore how students understand and process formative feedback and how they plan to use this information to inform next steps. We present findings from a study that examined students’ affective and cognitive responses to feedback, operationalized as emotions, interpretations (i.e., judgments, meaning making, attributions), and decision-making. Relationships among these processes and students’ initial motivational states were also explored. Survey data were collected from 93 students of a 7th grade English/Language Arts teacher who employed formative assessment practices. The results indicate that students tended to have positive emotions and judgments in response to their teacher’s feedback and make controllable attributions. They generally made informative meaning of the feedback and constructive decisions about next steps. Correlational findings showed that (1) emotions, judgments, meaning making, and attributions are related; (2) judgments of and the meaning that students made about the feedback were most strongly related to decision-making about next steps; and (3) task value was the only motivation variable related to responses to feedback. We conclude with implications for research and practice based on the expected and unexpected findings from this study.